Water in social imagination : from technological optimism to contemporary environmentalism - Costlow, Jane T. (Jane Tussey), 1955-; Haila, Yrjö; Rosenholm, Arja (Nature, Culture and Literature Ser., 2017)
Water in Social Imagination considers how human communities have known, imagined and shaped water - and how water has shaped both material culture and the imagination. Essays from diverse perspectives offer histories of water at different scales - from community water wells and sacred springs to Siberian rivers and the regulated space of the Baltic Sea. From early modernization through Soviet style technological optimism to contemporary environmentalism, water's ideological uses are multiple. With sustained attention not just to state policy and the technologies of high modernity, but to creative resistance to utilitarian imaginations, these essays insist on fluidities of meaning, ambiguities that derive both from water's physical mutability and from its dual nature as life necessity and agent of destruction.